COMPARATIVE ASSESSMENT OF ANTENATAL PREPARATION METHODS EFFICACY IN WOMEN WITH HIGHT-RISK PREGNANCY - Grabar, V.V.; Yacovenko, E.A.; Nazarenko, L.G.; Babadganyan, E.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The traditional antenatal preparation with estrogens is frequently not effective. In this study we applied desaminooxytocin or Pg Е1 (misoprostol) for induction of labour in patients of hight-risk pregnancy. Revealed that desaminooxytocin or prostaglandin E1 (intravaginal, intracervical or intrabuccal using) is more effective for decrease of frequency of delivery complications that estrogens. Prostaglandin E1 application is move preferable in case of hypertensive maternal disorders.